PENDAMPINGAN PERPAJAKAN TOUR AND TRAVEL - Rustam, Akie Rusaktiva; Widiastutik, Rika Nur (FKIP Universitas Wisnuwardhana, 2025)
The Community Service Activities carried out by PKM team of Accounting Department, FEB Universitas Brawijaya aims to improve tax understanding and compliance. The implementation of PKM activities is carried out at Tour & Travel companies. Through intensive mentoring, the PKM team has succeeded in providing an in-depth understanding of tax regulations relevant to the travel business, including VAT, Income Tax Articles 21, 22, and 23. In addition, the PKM team also provides recommendations regarding the potential for implementing Income Tax Articles 25 and 29 to optimize the company's financial management. The results of this activity show that collaboration between academics and practitioners can make a significant contribution to improving the quality of human resources in the field of taxation and supporting business growth in the tourism sector.